Characterisation of the torsional behaviour of titanium metal matrix composite shafts - Lee, Yaw Chuan (2009)
Titanium Metal Matrix Composites (TiMMC) have been gaining momentum in the aerospace applications in the past two decades. The advantages of TiMMC include superior stiffness-to-weight and strength-to-weight ratios, compared to conventional aerospace steels. The low pressure shaft in the aeroengine is one of the components that could benefit from the superior material properties of TiMMC. Potentially, the use of TiMMC could provide a combination of higher torque density (higher torque for a given diameter) and lower weight for these shafts. However, little has been done to investigate the torsional behaviour of TiMMC shafts.